HORSE FLIES OF SREDNA GORA MOUNTAINS, BULGARIA - D. Ganeva (Trakia Journal of Sciences)
Based on the study on the composition of the tabanid fauna of the Sredna Gora Mountains and the summarized reference data 54 species and 2 subspecies of 10 genera have been identified: Silvius (1 species), Chrysops (4 species), Atylotus (4 species), Therioplectes (2 species and 1 subspecies), Hybomitra (5 species), Tabanus (23 species and 1 subspecies), Heptatoma (1 species), Haematopota (10 species), Dasyrhamphis (2 species) and Philipomyia (2 species). For the first time, data on the tabanid fauna of the Ihtimanska and Sashtinska Sredna Gora Mountains have been reported. For the Ihtimanska Sredna Gora Mountains 17 species of 4 genera have been identified: Atylotus (1 species), Tabanus (12 species), Haematopota (2 species) and Philipomyia (2 species), and for Sashtinska - 20 species of 6 genera: Chrysops (2 species), Atylotus (2 species), Hybomitra (1 species), Tabanus (12 species), Haematopota (2 species), and Philipomyia (1 species). The species Atylotus latistriatus Brauer in Br. & Bergenstamm, 1880, Tabanus spodopterus Meigen, 1820 and Philipomyia aprica (Meigen, 1820), registered in the Ihtimanska and the Sashtinska Sredna Gora Mountains have been reported for the first time for the fauna of the Sredna Gora Mountains.